PENERAPAN ASUHAN KEPERAWATAN KELUARGA DENGAN INTERVENSI ACUYOGA (ACUPRESSURE + YOGA) TERHADAP NYERI HAID PADA REMAJA DI RT.007/05 SEMPER BARAT - Nur Aulia Fikri (2022)
Pain during menstruation in adolescents is one of the problems that are often experienced by adolescents. Various ways are done to overcome menstrual pain in adolescents both pharmacologically and non-pharmacologically. ACUYOGA is a combination of acupressure and yoga that is used to treat menstrual pain. The purpose of implementing this nursing care is to determine benefit of ACUYOGA in reducing menstrual pain in adolescents. The ACUYOGA therapeutic innovation intervention is applied to the main managed clients and resume clients who experience menstrual pain during menstruation. The implementation of ACUYOGA therapy is carried out for three consecutive days during the first to third day of the menstrual process. The results of the application of the ACUYOGA therapy intervention showed that after being given ACUYOGA therapy for three consecutive days menstrual pain in managed clients decreased from a scale of 5 to a scale of 1 and on a client's resume decreased from a scale of 4 to a scale of 1. The average decrease in pain scale after each therapy was completed. are 1. The conclusion from the application of nursing care is that ACUYOGA therapy is proven to be effective in reducing the menstrual pain scale in adolescents. Community nurses are expected to be able to make ACUYOGA therapy as one of the therapeutic options to overcome the problem of menstrual pain in adolescents.